Tacrine First-Phase Biotransformation and Associated Hepatotoxicity: A Possible Way to Avoid Quinone Methide Formation - Novak, Martin; Vajrychova, Marie; Koutsilieri, Stefania; Sismanoglou, Despoina-Christina; Kobrlova, Tereza; Prchal, Lukas; Svobodova, Barbora; Korabecny, Jan; Zarybnicky, Tomas; Raisova-Stuchlikova, Lucie; Skalova, Lenka; Lauschke, Volker M; et al. (ACS chemical biology, 2023)
Tacrine was withdrawn from clinical use as a drug against Alzheimer's disease in 2013, mainly due to drug-induced liver injury. The culprit of tacrine-associated hepatotoxicity is believed to be the 7-OH-tacrine metabolite, a possible precursor of quinone methide (Qmeth), which binds to intracellular -SH proteins. In our study, several different animal and human models (liver microsomes, primary hepatocytes, and liver slices) were used to investigate the biotransformation and hepatotoxicity of tacrine and its 7-substituted analogues (7-methoxy-, 7-phenoxy-, and 7-OH-tacrine). Our goal was to find the most appropriate in vitro model for studying tacrine hepatotoxicity and, through rational structure modifications, to develop derivatives of tacrine that are less prone to Qmeth formation. Our results show that none of animal models tested accurately mimic human tacrine biotransformation; however, the murine model seems to be more suitable than the rat model. Tacrine metabolism was overall most accurately mimicked in three-dimensional (3D) spheroid cultures of primary human hepatocytes (PHHs). In this system, tacrine and 7-methoxytacrine were hydroxylated to 7-OH-tacrine, whereas 7-phenoxytacrine formed, as expected, only trace amounts. Surprisingly, however, our study showed that 7-OH-tacrine was the least hepatotoxic (7-OH-tacrine < tacrine < 7-methoxytacrine < 7-phenoxytacrine) even after doses had been adjusted to achieve the same intracellular concentrations. The formation of Qmeth-cysteine and Qmeth-glutathione adducts after human liver microsome incubation was confirmed by all of the studied tacrine derivatives, but these findings were not confirmed after incubation with 3D PHH spheroids. Therefore, the presented data call into question the suggested previously hypothesized mechanism of toxicity, and the results open new avenues for chemical modifications to improve the safety of novel tacrine derivatives.
Keywords: Indolequinones; methamfetamin; Mice; biotransformace; Rats; Biotransformation; indolochinony; Animals; lékové postižení jater; takrin; krysa rodu Rattus; Humans; Tacrine; lidé; Chemical and Drug Induced Liver Injury; zvířata; myši; Methamphetamine